Osteomyelitis of the pubic symphysis caused by methicillin-resistant Staphylococcus aureus after vaginal delivery: a case report and literature review - Stefano Cosma; Fulvio Borella; Andrea Carosso; Agata Ingala; Federica Fassio; Tiziana Robba; Aldo Maina; Luca Bertero; Chiara Benedetto (BMC Infectious Diseases, 2019)
Abstract Background Osteomyelitis of the pubic symphysis is a rare cause of pelvic pain after delivery, mainly caused by Staphylococcus aureus and Pseudomonas aeruginosa. The clinical context is the same as the more common diastasis of the pubic bone, but the presence of intense local pain in association with fever should prompt further clinical work-up based on blood chemistry, microbiology and diagnostic imaging. We report the first case of methicillin-resistant Staphylococcus aureus osteomyelitis of the pubic symphysis occuring after the delivery. Case presentation A 39-year-old woman developed pain over the pubic bone 12 h after the delivery. After 72 h fever rose and laboratory examination showed elevation of C-reactive protein and procalcitonin levels. Pelvic x-rays and magnetic resonance showed pubic diastasis, joint effusion, tiny irregularities of articular surfaces and, severe bone edema. The patient was started on broad spectrum intravenous (IV) antibiotics (piperacillin-tazobactam) and then replaced to IV vancomycin and oral levofloxacin based on antibiogram result. She was then discharged with oral antibiotic therapy and fully recovered. Conclusions Due to the rarity of this disease, we compared our experience with the other cases of osteomyelitis of pubic symphysis occurring in peri-postpartum reported in the literature. The course of osteomyelitis was favourable in all patients, and only in one case an additional orthopedic procedure for symphysis fixation was necessary. Knowledge of this rare condition is important to enable prompt diagnosis and treatment.